3D cell culture based on artificial cells and hydrogel under microgravity for bottom-up microtissue constructs - Long, Ruimin; Shi, Linrong; He, Peng; Tian, Jumei; Wang, Shibin; Zheng, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
The use of hydrogel as a filling medium to recombine dispersed microencapsulated cells to form an embedded gel-cell microcapsule complex is a new idea based on bottom-up tissue construction, which is benefit for cell distribution and of great significance for tissue construction research in vitro. In this experiment, sodium alginate and chitosan were used as the main materials, rat normal liver cell BRL-3A was used as the model cell to prepare “artificial cells”. Silkworm pupa was used as raw material to extract silk fibroin solution, which was prepared by ultrasound to be the silk fibroin gel; silk fibroin hydrogel-microencapsulated hepatocyte embedded complex was then prepared by using silk fibroin gel as filling medium; the complex was cultured under three modes (static, shaking, and 3D microgravity), and the tissue forming ability of rat hepatocytes was investigated. The results showed that the microgravity culture condition can enhance the cell proliferation and promote the formation of cell colonies in the microcapsules; silk fibroin can form an embedded gel-cell microcapsule complex with microencapsulated cells, which provided mechanical support for the structure of the composite. We hope that this bottom-up construction system will have potential applications in the fields of cell culture and tissue construction.